PERANAN PEMAHAMAN PETUNJUK OPERASIONAL DALAM PROGRAM BORLAND DELPHI DAN KESERINGAN BERLATIH TERHADAP KEMAMPUAN MENGOPERASIKAN PROGRAM BORLAND DELPHI1 - Suyono .; Indriati . (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
The course of Database System includes theory and practice . Consequently the students should master the theory before, they do the practice. The theory is provided by the course with a course book of Borland Delphy programming database system. The Borland Delpy program provides the operational instructions in English. To operate the program then they should understand the instructions. By understanding the instructions hopefully they can operate the program to produce listing of program codes and component graphs. To aquire the skill, they need to practice. The question undert study is which variable plays more significantly in acquiring the skill, their understanding the English instructions or their practice frequency. To find out the answer an ex post facto study was conducted at PGRI University Semarang to undergraduate students majoring in Information Technology Education, PMIPATI Faculty who were taking the course of Database System at semester 3. There were 2 classes with 21 students in each class, 16 of which were included in the study, so there were 32 participants of the study. There were 3 types of data in the study: (1) the data of the students skill in understanding Borland Delhpy Program operational instructions in English, (2) the data of practice frequency, and (3) the data of the mastery of operating Borland Delphy program. The first two data were collected bu using tests, and the third was collected by using a questionairre. It can be concluded from the follow up analyses and the partial correlation coefficient test that ability to understand English instructions in Borland Delphy program had a significant role in the ability to operate it. It was proven by the follow up analysis of t1=5,385>tsig.5%=2,04. It resulted from the course book in Indonesian they used as well as their paying attention to the operational instructionals of the program in English. On the other hand the practice frequency did not significantly contribute to the skill. It was confirmed by the follow up analysis of t2=-0,029<tsig.5% =2,04. It means the less they practice, the less skillful they were in operating the program and in understanding the English instructions of the Borland Delphy program. Keywords : The Role, Understanding, Practicing, Abitlity, The Borland Delphi Program